2010
DOI: 10.1371/journal.pone.0009861
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Pluripotency-Associated Genes in Mesodermal Progenitor Cells (MPCs)

Abstract: BackgroundWe recently characterized a progenitor of mesodermal lineage (MPCs) from the human bone marrow of adults or umbilical cord blood. These cells are progenitors able to differentiate toward mesenchymal, endothelial and cardiomyogenic lineages. Here we present an extensive molecular characterization of MPCs, from bone marrow samples, including 39 genes involved in stem cell machinery, differentiation and cell cycle regulation.Methodology/Principal FindingsMPCs are cytofluorimetrically characterized and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Moreover, MPCs showed expression of pluripotency-associated markers and Nestin, all rapidly lost during mesengenic differentiation 7 . Sprouting assay revealed MPC ability to invade murine ECM protein gel.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MPCs showed expression of pluripotency-associated markers and Nestin, all rapidly lost during mesengenic differentiation 7 . Sprouting assay revealed MPC ability to invade murine ECM protein gel.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Nonetheless, the initial enthusiasm about mesodermal differentiation potential of MPCs is actually waning. In fact, after more than 7 years of studies on MPCs, mesengenic and angiogenic potential have been extensively described [5][6][7][8][9] , but differentiation toward any other cells of mesodermal origin is still lacking. Thus, here we propose a new, and more rigorous, definition of these cells as "Mesangiogenic Progenitor Cells", maintaining the acronym MPCs.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Sall4 is expressed in extraembryonic endoderm cells, which are stem cells that do not express Oct4 (Lim et al, 2008), fetal liver stem/progenitor cells but not adult liver stem cells (Oikawa et al, 2009), neural crest stem cells (Barembaum and BronnerFraser, 2010), mesoderm progenitor cells (Pacini et al, 2010), hematopoietic stem cells (Yang et al, 2007), endometrium cells (Forte et al, 2009), parathyroid gland stem cells (Shih et al, 2009), and multipotent adult progenitor cells (Ulloa-Montoya et al, 2007), but is not expressed in fully differentiated cells. As expected, Sall4 is expressed in cells of adult mouse ovaries and testes (Kohlhase et al, 2002).…”
Section: Expression Pattern Of Sall4 During Epimorphic Limb Regenerationmentioning
confidence: 99%
“…These proteins are essential for generation and maintenance of the ES cell identity by forming an auto-regulatory network that controls the expression and repression of pluripotency-and differentiation-associated genes respectively (Boyer et al 2005). Although a key pluripotency mediator in ES cells, several studies have reported the expression of OCT4 in unmanipulated and cultured somatic tissues (Zhao et al 2007, Kristensen et al 2010, Pacini et al 2010.…”
Section: Introductionmentioning
confidence: 99%